2021
DOI: 10.3389/fnsys.2021.762096
|View full text |Cite
|
Sign up to set email alerts
|

Return of the Righting Reflex Does Not Portend Recovery of Cognitive Function in Anesthetized Rats

Abstract: As the number of individuals undergoing general anesthesia rises globally, it becomes increasingly important to understand how consciousness and cognition are restored after anesthesia. In rodents, levels of consciousness are traditionally captured by physiological responses such as the return of righting reflex (RORR). However, tracking the recovery of cognitive function is comparatively difficult. Here we use an operant conditioning task, the 5-choice serial reaction time task (5-CSRTT), to measure sustained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…While the righting reflex is a well-established measure of anesthetic effects in rodents ( 50 ), it has some notable limitations ( 51 , 52 ). To eliminate these potential confounds, we confirmed our results using the adhesive sticker removal test ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…While the righting reflex is a well-established measure of anesthetic effects in rodents ( 50 ), it has some notable limitations ( 51 , 52 ). To eliminate these potential confounds, we confirmed our results using the adhesive sticker removal test ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the study investigated anesthesia-specific parameters, including induction time and duration. Induction time, defined as the time from the administration of anesthesia to the loss of the righting reflex, is a critical measure of anesthetic efficiency [22] . In our study, the XK group demonstrated a shorter induction experienced by the animals.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, after anesthesia treatment, rats' performance on the 5-choice serial reaction time task (table 1) returned to preanesthesia levels within 1 to 3 h depending on the dose and type of anesthetic used. 37,43 However, performance on this task had no correlation with the return of righting reflex, indicating that recovery of cognitive function cannot be predicted from a righting reflex assay. Additional tests have been developed to assess behavioral changes in mice due to postoperative delirium.…”
Section: Assessing Reversal Of and Recovery From General Anesthesiamentioning
confidence: 98%
“…109 However, as noted previously, by measuring only the righting reflex, these experiments typically only probe the hypnotic component of general anesthesia, and ignore behavioral responsiveness readouts. Additionally, return of the righting reflex does not mean an animal has recovered its cognitive abilities, 43 which places doubt on whether stimulating cholinergic systems can reverse general anesthesia beyond restoring postural control and locomotion. For example, general anesthetics such as propofol disrupt cortical connectivity 110 while increasing the spectral power of slow (1 to 4 Hz) oscillations, 111 so it might be expected that cholinergic stimulation could return these parameters to baseline, but this is not the case.…”
Section: Stimulating Arousal Systems and Emergence From General Anest...mentioning
confidence: 99%
See 1 more Smart Citation